Interferon Control of the Sterol Metabolic Network: Bidirectional Molecular Circuitry-Mediating Host Protection - Robertson, Kevin A.; Ghazal, Peter (Frontiers in Immunology, 2016)
The sterol metabolic network is emerging centre-stage in inflammation and immunity. Historically, observational clinical studies show hypocholesterolemia is a common side effect of interferon treatment. More recently, comprehensive systems-wide investigations of the macrophage interferon response reveal a direct molecular link between cholesterol metabolism and infection.  Upon infection, flux through the sterol metabolic network is acutely moderated by the interferon response at multiple regulatory levels. The precise mechanisms by which interferon regulates the mevalonate-sterol pathway – the spine of the network - are beginning to be unraveled. In this review, we discuss our current understanding of the multifactorial mechanisms by which interferon regulates the sterol pathway. We also consider bidirectional communications resulting in sterol metabolism regulation of immunity. Finally, we deliberate on how this fundamental interaction functions as an integral element of host protective responses to infection and harmful inflammation.